Matrine Exerts Hepatotoxic Effects via the ROS-Dependent Mitochondrial Apoptosis Pathway and Inhibition of Nrf2-Mediated Antioxidant Response. (14th October 2019) - You, Longtai; Yang, Chunjing; Du, Yuanyuan; Liu, Yi; Chen, Gongsen; Sai, Na; Dong, Xiaoxv; Yin, Xingbin; Ni, Jian
Abstract : Matrine, an alkaloid isolated from Sophora flavescens, possesses a wide range of pharmacological properties. However, the use of matrine in clinical practice is limited due to its toxic effects. The present study investigated the roles of mitochondria and reactive oxygen species (ROS) in matrine-induced liver injury. Our results showed that treatment of HL-7702 cells with matrine led to significant and concentration- and time-dependent reductions in their viability, as well as significant and concentration-dependent increases in the number of apoptotic cells and supernatant lactate dehydrogenase (LDH) activity. The treatment led to significant increases in the population of cells in S phase and significant reduction of cell proportion in G0/G1 and G2/M phases. It also significantly and concentration-dependently increased the levels of ROS and malondialdehyde (MDA) but significantly and concentration-dependently reduced superoxide dismutase (SOD) activity, level of reduced glutathione (GSH), and mitochondrial membrane potential (MMP). Matrine treatment significantly and concentration-dependently upregulated the expressions of Bax, p53, p-p53, p21, cyclin E, Fas, cleaved caspase-3, caspase-8, and caspase-9 proteins and downregulated the expressions of Bcl-2, cyclin-dependent kinase 2 (CDK2), and cyclin A. It also significantly promoted the cleavage of poly(ADP-ribose)polymerase (PARP), upregulated Kelch-like ECH-associated protein 1 (Keap1) expression, and downregulated the expressions of cellular total and nuclear Nrf2. Matrine significantly inhibited the expressions of downstream oxidoreductases (Heme oxygenase-1 (HO-1) and NAD(P)H:quinone oxidoreductases 1 (NQO-1)) and enhanced the formation of Keap1/Nrf2 protein complex. These results show that the hepatotoxic effect of matrine is exerted via inhibition of Nrf2 pathway, activation of ROS-mediated mitochondrial apoptosis pathway, and cell cycle arrest at S phase. Pretreatment with N-acetyl cysteine (NAC) partially reversed matrine-induced hepatotoxicity.